Rolling bearings

The rolling bearing with a specialized steel composition and microstructure addresses durability issues by enhancing resistance to hydrogen embrittlement and wear, improving performance under conditions of oil film breakage.

JP7603521B2Active Publication Date: 2024-12-20NTN CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021077618
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-04-30
Publication Date
2024-12-20
Estimated Expiration
2041-04-30

AI Technical Summary

Technical Problem

Rolling bearings using existing bearing parts face durability issues under conditions where one ring rotates relative to another, leading to potential oil film breakage and early peeling due to hydrogen embrittlement.

Method used

The rolling bearing is composed of an inner and outer ring, with a surface layer containing specific steel compositions and microstructural features, including martensitic block grains, precipitates, and retained austenite, designed to withstand conditions of oil film depletion, featuring high hardness and resistance to hydrogen embrittlement.

Benefits of technology

The bearing exhibits improved durability by preventing wear and early peeling under conditions of oil film breakage, with enhanced resistance to hydrogen embrittlement and improved shear resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007603521000008
    Figure 0007603521000008
  • Figure 0007603521000009
    Figure 0007603521000009
  • Figure 0007603521000010
    Figure 0007603521000010
Patent Text Reader

Abstract

To provide a rolling bearing of which the durability is improved against hydrogen embrittlement under the conditions that oil film shortage easily occurs.SOLUTION: A rolling bearing includes an inner ring, an outer ring, and rolling elements. The rolling bearing is mounted to a mechanical structure in which the inner ring is positively / reversely rotated relative to the outer ring or the inner ring is rotated relative to the outer ring from the static state. At least one of the inner ring, the outer ring, and the rolling elements is made of steel, and has a surface layer part as a region having a distance up to 20 μm from the surface. The steel includes carbon having 0.70 mass % to 1.10 mass %, silicon having 0.15 mass % to 0.35 mass %, manganese having 0.30 mass % to 0.60 mass %, chrome having 1.30 mass % to 1.60 mass %, vanadium having 0.50 mass % or smaller, and molybdenum having 0.50 mass % or smaller, and the rest is iron and inevitable impurities.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a rolling bearing. [Background technology]

[0002] Patent Document 1 (Japanese Patent No. 5489111) describes a bearing part. The bearing part described in Patent Document 1 is formed by subjecting a steel workpiece to nitriding, quenching, and tempering. The bearing part described in Patent Document 1 has high wear resistance because cementite is dispersed in the steel of the surface layer.

[0003] Patent Document 2 (Japanese Patent No. 6023422) describes a bearing part. The bearing part described in Patent Document 2 is formed by subjecting a steel workpiece to nitriding, quenching, and tempering. The bearing part described in Patent Document 2 has a large amount of retained austenite in the steel of the surface layer, and therefore has high durability against impression-initiated peeling under lubrication with foreign matter contamination. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 5489111 [Patent Document 2] Patent No. 6023422 Summary of the Invention [Problem to be solved by the invention]

[0005] As a result of intensive research by the present inventors, the bearing component described in Patent Document 1 and the bearing component described in Patent Document 2 have room for further improvement in durability. In particular, rolling bearings using the bearing components described in Patent Document 1 and Patent Document 2 have room for improvement in durability when used under conditions in which one raceway rotates forward and backward relative to the other raceway, or one raceway rotates relative to the other raceway from a stationary state, and oil film breakdown is likely to occur. Under conditions in which oil film breakdown is likely to occur, early flaking due to hydrogen embrittlement is likely to occur. The present invention provides a rolling bearing with improved durability against hydrogen embrittlement under conditions in which oil film breakdown is likely to occur. [Means for solving the problem]

[0006] The rolling bearing of the present invention comprises an inner ring, an outer ring, and rolling elements. The rolling bearing is attached to a machine structure in which the inner ring rotates forward and backward relative to the outer ring, or the inner ring rotates relative to the outer ring from a stationary state. At least one of the inner ring, the outer ring, and the rolling elements is made of steel and has a surface layer portion that is a region up to 20 μm away from the surface. The steel contains 0.70 mass percent to 1.10 mass percent carbon, 0.15 mass percent to 0.35 mass percent silicon, 0.30 mass percent to 0.60 mass percent manganese, 1.30 mass percent to 1.60 mass percent chromium, 0.50 mass percent or less vanadium, and 0.50 mass percent or less molybdenum, with the balance being iron and unavoidable impurities. The steel of the surface layer portion has martensite block grains and precipitates. The precipitates are nitrides containing chromium or vanadium as a main component, or carbonitrides containing chromium or vanadium as a main component. In the steel of the surface layer, the average grain size of the martensite block grains at a comparative area ratio of 30 percent is 2.0 μm or less.

[0007] The rolling bearing may be used under conditions in which the oil film parameter is less than 1.2. The rolling bearing may be used under conditions in which the dn value is 200,000 or less.

[0008] The rolling bearing may be a tapered roller bearing.The rolling bearing may be a spherical roller bearing.The rolling bearing may have a diamond-like carbon coating or an iron oxide coating formed on the surface.

[0009] In the above rolling bearing, the steel may contain 0.90 mass percent or more and 1.10 mass percent or less of carbon, 0.20 mass percent or more and 0.30 mass percent or less of silicon, 0.40 mass percent or more and 0.50 mass percent or less of manganese, 1.40 mass percent or more and 1.60 mass percent or less of chromium, 0.20 mass percent or more and 0.30 mass percent or less of vanadium, and 0.10 mass percent or more and 0.30 mass percent or less of molybdenum, with the remainder being iron and unavoidable impurities.

[0010] In the rolling bearing, an area ratio of precipitates in the steel of the surface layer portion may be 2.0 percent or more.

[0011] In the rolling bearing, the maximum grain size of precipitates in the steel surface layer may be 0.5 μm or less.

[0012] In the rolling bearing, the steel of the surface layer may further contain cementite. The maximum grain size of the cementite in the steel of the surface layer may be 1.5 μm or less.

[0013] In the above rolling bearing, the nitrogen concentration in the steel of the surface layer may be 0.15 mass percent or more.

[0014] In the rolling bearing, the volume ratio of retained austenite in the steel at a position 50 μm away from the surface may be 15 percent or more.

[0015] In the rolling bearing, the hardness of the steel may be 58HRC or more at a position 50 μm away from the surface.

[0016] In the rolling bearing, the volume ratio of retained austenite in the steel at a position 50 μm away from the surface may be 25 percent or more and 35 percent or less.The hardness of the steel at a position 50 μm away from the surface may be 58 HRC or more and 64 HRC or less. Effect of the Invention

[0017] According to the rolling bearing of the present invention, it is possible to improve durability against hydrogen embrittlement under conditions where oil film breakdown is likely to occur. [Brief description of the drawings]

[0018] [Figure 1] FIG. [Diagram 2] FIG. 2 is an enlarged view of II in FIG. [Diagram 3] 3A to 3C are process diagrams showing a manufacturing method of the inner ring 10. [Figure 4] 1 is a cross-sectional view of a rolling bearing 100. FIG. [Diagram 5] FIG. 2 is a cross-sectional view of a rolling bearing 100A. [Figure 6] FIG. 2 is a cross-sectional view of the axle device 200. [Figure 7] 13 is a graph showing measurement results of nitrogen concentration and carbon concentration in the vicinity of the raceway surface of the race washer of Sample 1. [Figure 8] 13 is a graph showing measurement results of nitrogen concentration and carbon concentration in the vicinity of the raceway surface of the race washer of Sample 2. [Figure 9] 1 is an SEM image of the surface layer of the race of Sample 1. [Figure 10] This is an SEM image of the surface layer of the race of sample 2. [Figure 11] This is an EBSD phase map of the surface layer of the race of Sample 1. [Figure 12] This is an EBSD phase map of the surface layer of the race of sample 2. [Figure 13] FIG. 11 is an EBSD phase map of the surface layer of the race of sample 3. [Figure 14] 4 is a bar graph showing the average grain size of martensite block grains in the surface layer portions of the races of Samples 1 to 3. [Figure 15] 1 is a graph showing the results of a rolling fatigue life test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The details of the embodiments of the present invention will be described with reference to the drawings. Here, the same or corresponding parts are designated by the same reference numerals, and redundant description will not be repeated.

[0020] The bearing component according to the embodiment is, for example, an inner ring 10 of a rolling bearing. In the following, the inner ring 10 will be described as an example of the bearing component according to the embodiment. However, the bearing component according to the embodiment is not limited to this. The bearing component according to the embodiment may be an outer ring of a rolling bearing or a rolling element of a rolling bearing.

[0021] (Configuration of inner ring 10) Fig. 1 is a cross-sectional view of the inner ring 10. As shown in Fig. 1, the inner ring 10 is ring-shaped. The central axis of the inner ring 10 is defined as central axis A. The inner ring 10 has a width surface 10a, a width surface 10b, an inner peripheral surface 10c, and an outer peripheral surface 10d. The width surface 10a, the width surface 10b, the inner peripheral surface 10c, and the outer peripheral surface 10d form the surface of the inner ring 10.

[0022] In the following, the direction of the central axis A is referred to as the axial direction. Also, in the following, the direction along the circumference centered on the central axis A when viewed along the axial direction is referred to as the circumferential direction. Furthermore, in the following, the direction perpendicular to the axial direction is referred to as the radial direction.

[0023] The width surface 10a and the width surface 10b are end surfaces in the axial direction of the inner ring 10. The width surface 10b is the surface opposite to the width surface 10a in the axial direction.

[0024] The inner peripheral surface 10c extends in the circumferential direction. The inner peripheral surface 10c faces the central axis A. One end of the inner peripheral surface 10c in the axial direction is connected to the width surface 10a, and the other end of the inner peripheral surface 10c is connected to the width surface 10b. The inner ring 10 is fitted onto a shaft (not shown) at the inner peripheral surface 10c.

[0025] The outer peripheral surface 10d extends in the circumferential direction. The outer peripheral surface 10d faces the opposite side to the central axis A. In other words, the outer peripheral surface 10d is the opposite side to the inner peripheral surface 10c in the radial direction. The outer peripheral surface 10d is continuous with the width surface 10a at one end in the axial direction and continuous with the width surface 10b at the other end in the axial direction.

[0026] The outer peripheral surface 10d has a raceway surface 10da. The raceway surface 10da extends in the circumferential direction. The outer peripheral surface 10d is recessed toward the inner peripheral surface 10c at the raceway surface 10da. In a cross-sectional view, the raceway surface 10da has a partially circular shape. The raceway surface 10da is located at the center of the outer peripheral surface 10d in the axial direction. The raceway surface 10da is a part of the outer peripheral surface 10d that contacts the rolling elements (not shown in FIG. 1).

[0027] The inner ring 10 is made of steel. More specifically, the inner ring 10 is made of steel that has been hardened and tempered. The steel that constitutes the inner ring 10 contains 0.70 to 1.10 percent by mass carbon, 0.15 to 0.35 percent by mass silicon, 0.30 to 0.60 percent by mass manganese, 1.30 to 1.60 percent by mass chromium, 0.50 to 0.50 percent by mass vanadium, and 0.50 to 0.50 percent by mass molybdenum. In this steel, the molybdenum content is 0.01 percent by mass or more, and the vanadium content is 0.01 percent by mass or more.

[0028] The carbon content of the steel constituting the inner ring 10 is 0.70 mass percent or more in order to improve hardness, and the carbon content of the steel constituting the inner ring 10 is 1.10 mass percent or less in order to suppress quench cracking.

[0029] The silicon content of the steel constituting the inner ring 10 is 0.15 mass percent or more in order to increase temper softening resistance and improve workability, while the silicon content of the steel constituting the inner ring 10 is 0.35 mass percent or less because an excessive amount of silicon actually reduces workability.

[0030] The manganese content of the steel constituting the inner ring 10 is 0.30 mass percent or more in order to ensure hardenability, and the manganese content of the steel constituting the inner ring 10 is 0.60 mass percent or less because an excessive amount of manganese increases manganese-based nonmetallic inclusions in the steel.

[0031] The chromium content of the steel constituting the inner ring 10 is 1.30 mass percent or more in order to ensure hardenability and to form nitrides and carbonitrides, while the chromium content of the steel constituting the inner ring 10 is 1.60 mass percent or less in order to inhibit the formation of coarse precipitates.

[0032] Vanadium is included in the steel constituting the inner ring 10 in order to refine nitrides and carbonitrides. The vanadium content of the steel constituting the inner ring 10 is 0.50 mass percent or less in order to suppress the increase in cost associated with the addition of vanadium.

[0033] Molybdenum is contained in the steel constituting the inner ring 10 in order to refine nitrides and carbonitrides and to improve hardenability. The molybdenum content in the steel constituting the inner ring 10 is 0.50 mass percent or less in order to suppress the increase in cost associated with the addition of molybdenum.

[0034] The steel constituting the inner ring 10 may contain 0.90 to 1.10 mass percent carbon, 0.20 to 0.30 mass percent silicon, 0.40 to 0.50 mass percent manganese, 1.40 to 1.60 mass percent chromium, 0.20 to 0.30 mass percent vanadium, and 0.10 to 0.30 mass percent molybdenum. The remainder of the steel constituting the inner ring 10 is iron and unavoidable impurities.

[0035] Fig. 2 is an enlarged view of II in Fig. 1. As shown in Fig. 2, the region of the inner ring 10 up to a distance of 20 µm from the surface constitutes the surface layer portion 11. The surface of the inner ring 10 is subjected to, for example, nitriding treatment. As a result, the nitrogen concentration in the steel of the surface layer portion 11 is, for example, 0.15 mass percent or more. The nitrogen concentration in the steel of the surface layer portion 11 is preferably 0.20 mass percent or more and 0.30 mass percent or less. The nitrogen concentration in the steel of the surface layer portion 11 is measured using an EPMA (Electron Probe Micro Analyzer).

[0036] Precipitates are dispersed in the steel of the surface layer portion 11. The precipitates are nitrides containing chromium or vanadium as a main component, or carbonitrides containing chromium or vanadium as a main component.

[0037] A nitride containing chromium (vanadium) as a main component is a nitride of chromium (vanadium) or a nitride in which some of the chromium (vanadium) sites are replaced by an alloying element other than chromium (vanadium).

[0038] Chromium (vanadium)-based carbonitrides are chromium (vanadium) carbides in which some of the carbon sites are replaced by nitrogen. The chromium (vanadium) sites of chromium (vanadium)-based carbonitrides may be replaced by alloy elements other than chromium (vanadium).

[0039] The area ratio of the precipitates in the steel of the surface layer portion 11 is preferably 2.0 percent or less. The maximum grain size of the precipitates in the steel of the surface layer portion 11 is preferably 0.5 μm or less.

[0040] The area ratio and maximum grain size of precipitates in the steel of the surface layer portion 11 are measured by the following method. First, a cross-sectional image (hereinafter referred to as "SEM image") is obtained using a SEM (Scanning Electron Microscope) at a cross section of the inner ring 10 including the surface layer portion 11. The magnification for obtaining this SEM image is 15,000 times.

[0041] Second, the acquired SEM image is subjected to image processing. More specifically, since the precipitates appear white in the SEM image, the area of ​​each of the white parts in the SEM image and the total area are calculated by image processing.

[0042] The total area of ​​the white parts in the SEM image is regarded as the area ratio of precipitates in the steel of the surface layer portion 11. The square root of the maximum area of ​​each white part in the SEM image divided by π / 4 is regarded as the maximum grain size of precipitates in the steel of the surface layer portion 11.

[0043] Cementite (Fe3C) may be further dispersed in the steel of the surface layer portion 11. A part of the iron sites in the cementite may be substituted with an alloying element, and a part of the carbon sites in the cementite may be substituted with nitrogen. The maximum grain size of the cementite in the steel of the surface layer portion 11 is preferably 1.5 μm or less.

[0044] The maximum grain size of cementite in the steel of the surface layer portion 11 is measured by the following method. First, an SEM image is acquired of a cross section of the inner ring 10 including the surface layer portion 11. The magnification for acquiring this SEM image is 15,000 times. Second, image processing is performed on the acquired SEM image. More specifically, since cementite appears as an elliptical gray portion in the SEM image, the area of ​​each of the elliptical gray portions in the SEM image is calculated by image processing. Then, the square root of the maximum value of the area of ​​each of the elliptical gray portions in the SEM image divided by π / 4 is regarded as the maximum grain size of cementite in the steel of the surface layer portion 11.

[0045] The volume ratio of the retained austenite in the steel at a position 50 μm away from the surface of the inner ring 10 is preferably 15 percent or more. The volume ratio of the retained austenite in the steel at a position 50 μm away from the surface of the inner ring 10 is more preferably 25 percent or more and 35 percent or less.

[0046] The volume ratio of the retained austenite in steel is measured by X-ray diffraction, that is, the volume ratio of the retained austenite in steel is calculated by comparing the integrated intensity of the diffraction peak in X-ray diffraction of austenite with the integrated intensity of the diffraction peak in X-ray diffraction of phases other than austenite.

[0047] The hardness of the steel is preferably 58HRC or more at a position 50μm away from the surface of the inner ring 10. It is more preferable that the hardness of the steel is 58HRC or more and 64HRC or less at a position 50μm away from the surface of the inner ring 10. The hardness of the steel is measured according to the Rockwell hardness test method defined in the JIS standard (JIS Z 2245:2016).

[0048] The steel of the surface layer portion 11 has martensite block grains. The difference in crystal orientation between two adjacent martensite block grains at the grain boundary is 15° or more. From another perspective, even if there is a location where the crystal orientation is misaligned, if the difference in crystal orientation is less than 15°, the location is not considered to be a grain boundary of the martensite block grains. The grain boundary of the martensite block grains is determined by EBSD (Electron Back Scattered Diffraction) method.

[0049] In the steel of the surface layer 11, the average grain size of the martensite block grains is 2.0 μm or less when the comparative area ratio is 30 percent. In the steel of the surface layer 11, the average grain size of the martensite block grains is preferably 1.5 μm or less when the comparative area ratio is 50 percent.

[0050] The average grain size of the martensite block grains at a comparative area ratio of 30 percent (50 percent) is measured by the following method. First, a cross-sectional observation is performed on a cross-section of the inner ring 10 including the surface layer portion 11. At this time, the martensite block grains included in the observation field are identified by the EBSD method. This observation field is an area of ​​50 μm × 45 μm. Second, the area of ​​each of the martensite block grains included in the observation field is analyzed from the crystal orientation data obtained by the EBSD method.

[0051] Third, the areas of the martensite block grains included in the observation field are added up in descending order of area. This addition is continued until the total area of ​​the martensite block grains included in the observation field reaches 30 percent (50 percent). The equivalent circle diameter is calculated for each of the martensite block grains that have been added up. This equivalent circle diameter is the square root of the area of ​​the martensite block grain divided by π / 4. The average of the equivalent circle diameters of the martensite block grains that have been added up is regarded as the average grain size of the martensite block grains when the comparison area ratio is 30 percent (50 percent).

[0052] (Manufacturing method of the inner ring 10) Fig. 3 is a process diagram showing a manufacturing method of the inner ring 10. As shown in Fig. 3, the manufacturing method of the inner ring 10 includes a preparation step S1, a nitriding step S2, a quenching step S3, a tempering step S4, and a post-treatment step S5. The nitriding step S2 is performed after the preparation step S1. The quenching step S3 is performed after the nitriding step S2. The tempering step S4 is performed after the quenching step S3. The post-treatment step S5 is performed after the tempering step S4.

[0053] In the preparation step S1, a workpiece to be processed is prepared. The workpiece to be processed is a ring-shaped member made of the same steel as the inner ring 10.

[0054] In the nitriding step S2, a nitriding treatment is performed on the surface of the workpiece by holding the workpiece in an atmosphere containing a nitrogen source (e.g., ammonia) at a temperature equal to or higher than the A1 transformation point of the steel constituting the workpiece.

[0055] In the quenching step S3, the workpiece is quenched. The quenching is performed by holding the workpiece at a temperature equal to or higher than the A1 transformation point of the steel constituting the workpiece, and then quenching the M of the steel constituting the workpiece. S The quenching step S3 is performed by quenching to a temperature below the transformation point. The heating and holding temperature in the quenching step S3 is preferably equal to or lower than the heating and holding temperature in the nitriding step S2. The quenching step S3 may be performed twice. The heating and holding temperature in the second quenching step S3 is preferably lower than the heating and holding temperature in the first quenching step S3. This allows fine and large amounts of precipitates to be dispersed in the surface layer of the processed member.

[0056] In the tempering step S4, the workpiece is tempered. Tempering is performed by holding the workpiece at a temperature below the A1 transformation point of the steel that constitutes the workpiece. In the post-treatment step S5, the surface of the workpiece is machined (grinded, polished), cleaned, etc. By the above steps, the inner ring 10 having the structure shown in Figs. 1 and 2 is formed.

[0057] In addition, since the precipitates are dispersed in a large amount and finely in the steel of the surface layer 11, the martensite block grains are less likely to grow large, and therefore, in the steel of the surface layer 11, the average grain size of the martensite block grains at a comparative area ratio of 30 percent is 2.0 μm or less.

[0058] (The effect of 10 inner circles) In the inner ring 10, martensite block grains are refined so that the average grain size at a comparative area ratio of 30 percent is 2.0 μm or less in the steel of the surface layer 11. As a result, the surface layer 11 of the inner ring 10 has high toughness, improving the shear resistance of the surface of the inner ring 10 that comes into contact with the rolling elements (specifically, the raceway surface 10da). In this way, the durability of the inner ring 10 is improved.

[0059] When the area ratio of precipitates in the steel of the surface layer 11 is 2.0 percent or more, i.e., when the precipitates are dispersed at high density in the steel of the surface layer 11, the shear resistance of the surface of the inner ring 10 that comes into contact with the rolling elements (specifically, the raceway surface 10da) is improved, thereby further improving durability.

[0060] When the maximum grain size of the precipitates in the steel of surface layer portion 11 is 0.5 μm, the precipitates are densely and finely dispersed in the steel of surface layer portion 11, improving the wear resistance and toughness and further improving the durability of inner ring 10. When the maximum grain size of cementite in the steel of surface layer portion 11 is 1.5 μm or less, the wear resistance and toughness of inner ring 10 are further improved due to the fine dispersion of cementite.

[0061] When the volume ratio of retained austenite in the steel at a position 50 μm away from the surface of the inner ring 10 is 15 percent or more (25 percent or more and 35 percent or less), durability against indentation-initiated spalling in an environment containing foreign matter is improved. When the hardness of the steel at a position 50 μm away from the surface of the inner ring 10 is 58 HRC or more (58 HRC or more and 64 HRC or less), the wear resistance of the inner ring 10 is further improved.

[0062] (Rolling bearing according to embodiment) A rolling bearing according to an embodiment (hereinafter referred to as "rolling bearing 100") will be described below.

[0063] Fig. 4 is a cross-sectional view of the rolling bearing 100. As shown in Fig. 4, the rolling bearing 100 is a deep groove ball bearing. However, the rolling bearing 100 is not limited to this. The rolling bearing 100 may be, for example, a thrust ball bearing. The rolling bearing 100 has an inner ring 10, an outer ring 20, rolling elements 30, and a cage 40.

[0064] The outer ring 20 has a width surface 20a, a width surface 20b, an inner peripheral surface 20c, and an outer peripheral surface 20d. The surface of the outer ring 20 is composed of the width surface 20a, the width surface 20b, the inner peripheral surface 20c, and the outer peripheral surface 20d.

[0065] The width surface 20a and the width surface 20b are end surfaces in the axial direction of the outer ring 20. The width surface 20b is the surface opposite to the width surface 20a in the axial direction.

[0066] The inner peripheral surface 20c extends in the circumferential direction. The inner peripheral surface 20c faces the central axis A. One end of the inner peripheral surface 20c in the axial direction is continuous with the width surface 20a, and the other end of the inner peripheral surface 20c in the axial direction is continuous with the width surface 20b. The outer ring 20 is disposed such that the inner peripheral surface 20c faces the outer peripheral surface 10d.

[0067] The inner peripheral surface 20c has a raceway surface 20ca. The raceway surface 20ca extends in the circumferential direction. The raceway surface 20ca of the inner peripheral surface 20c is recessed toward the outer peripheral surface 20d. In a cross-sectional view, the raceway surface 20ca has a partially circular shape. The raceway surface 20ca is located at the center of the inner peripheral surface 20c in the axial direction. The raceway surface 20ca is a part of the inner peripheral surface 20c that contacts the rolling elements 30.

[0068] The outer peripheral surface 20d extends in the circumferential direction. The outer peripheral surface 20d faces the opposite side to the central axis A. In other words, the outer peripheral surface 20d is the opposite surface to the inner peripheral surface 20c in the radial direction. One end of the outer peripheral surface 20d in the axial direction is continuous with the width surface 20a, and the other end of the outer peripheral surface 20d in the axial direction is continuous with the width surface 20b. The outer ring 20 is fitted into a housing (not shown) at the outer peripheral surface 20d.

[0069] The rolling elements 30 are spherical. The rolling elements 30 are disposed between the outer peripheral surface 10d (raceway surface 10da) and the inner peripheral surface 20c (raceway surface 20ca). The cage 40 is ring-shaped and disposed between the outer peripheral surface 10d and the inner peripheral surface 20c. The cage 40 holds the rolling elements 30 such that the interval between two adjacent rolling elements 30 in the circumferential direction is within a certain range.

[0070] The outer ring 20 and the rolling elements 30 may be formed from the same steel as the inner ring 10. In addition, the surface layer portion of the outer ring 20 (region up to 20 μm away from the surface of the outer ring 20) and the surface layer portion of the rolling elements 30 (region up to 20 μm away from the surface of the rolling elements 30) may have the same configuration as the surface layer portion 11.

[0071] (Modification) A rolling bearing 100 according to a modified example (hereinafter referred to as "rolling bearing 100A") will be described.

[0072] Fig. 5 is a cross-sectional view of the rolling bearing 100A. As shown in Fig. 5, the rolling bearing 100A is a tapered roller bearing. The rolling bearing 100A may be a self-aligning roller bearing. The rolling bearing 100A has an inner ring 110, an outer ring 120, a rolling element 130, and a cage 140.

[0073] The inner ring 110 has a width surface 110a, a width surface 110b, an inner peripheral surface 110c, and an outer peripheral surface 110d. The width surface 110a, the width surface 110b, the inner peripheral surface 110c, and the outer peripheral surface 110d form the surface of the inner ring 110. The inner diameter of the inner ring 110 is preferably 60 mm or more.

[0074] The width surface 110a and the width surface 110b are end surfaces in the axial direction of the inner ring 110. The width surface 110b is the surface opposite to the width surface 110a in the axial direction.

[0075] The inner peripheral surface 110c extends in the circumferential direction. The inner peripheral surface 110c faces the central axis A. One end of the inner peripheral surface 110c in the axial direction is continuous with the width surface 110a, and the other end of the inner peripheral surface 110c in the axial direction is continuous with the width surface 110b.

[0076] The outer peripheral surface 110d extends in the circumferential direction. The outer peripheral surface 110d faces the opposite side to the central axis A. In other words, the outer peripheral surface 110d is the opposite surface to the inner peripheral surface 110c in the radial direction. The outer peripheral surface 110d is continuous with the width surface 110a at one end in the axial direction, and is continuous with the width surface 110b at the other end in the axial direction. The outer peripheral surface 110d has a raceway surface 110da. The raceway surface 110da extends in the circumferential direction. The raceway surface 110da is a part of the outer peripheral surface 110d that contacts the rolling element 130.

[0077] The outer ring 120 has a width surface 120a, a width surface 120b, an inner peripheral surface 120c, and an outer peripheral surface 120d. The surface of the outer ring 120 is composed of the width surface 120a, the width surface 120b, the inner peripheral surface 120c, and the outer peripheral surface 120d.

[0078] The width surface 120a and the width surface 120b are end surfaces in the axial direction of the outer ring 120. The width surface 120b is the surface opposite to the width surface 120a in the axial direction.

[0079] The inner peripheral surface 120c extends in the circumferential direction. The inner peripheral surface 120c faces the central axis A. The inner peripheral surface 120c is connected to the width surface 120a at one end in the axial direction and is connected to the width surface 120b at the other end in the axial direction. The outer ring 120 is disposed such that the inner peripheral surface 120c faces the outer peripheral surface 10d. The inner peripheral surface 120c has a raceway surface 120ca. The raceway surface 120ca extends in the circumferential direction. The raceway surface 120ca is a part of the inner peripheral surface 120c that contacts the rolling element 130.

[0080] The outer peripheral surface 120d extends in the circumferential direction. The outer peripheral surface 120d faces the opposite side to the central axis A. In other words, the outer peripheral surface 120d is the opposite surface to the inner peripheral surface 120c in the radial direction. The outer peripheral surface 120d is continuous with the width surface 120a at one end in the axial direction and is continuous with the width surface 120b at the other end in the axial direction.

[0081] The rolling elements 130 are tapered rollers. The rolling elements 130 are disposed between the outer peripheral surface 110d (raceway surface 110da) and the inner peripheral surface 120c (raceway surface 120ca). The cage 140 is ring-shaped and disposed between the outer peripheral surface 110d and the inner peripheral surface 120c. The cage 140 holds the rolling elements 130 such that the interval between two adjacent rolling elements 130 in the circumferential direction is within a certain range.

[0082] The inner ring 110, the outer ring 120, and the rolling elements 130 may be formed of the same steel as the inner ring 10. The surface layer portion of the inner ring 110 (region up to 20 μm away from the surface of the inner ring 110), the surface layer portion of the outer ring 120 (region up to 20 μm away from the surface of the outer ring 120), and the surface layer portion of the rolling elements 130 (region up to 20 μm away from the surface of the rolling elements 130) may have the same configuration as the surface layer portion 11. The surfaces of the inner ring 110, the outer ring 120, and the rolling elements 130 may be subjected to surface modification such as forming a diamond-like carbon coating or forming an iron oxide (Fe3O4) coating (subjecting to black dyeing treatment).

[0083] The rolling bearing 100A is used, for example, in an axle device 200. The axle device 200 is, for example, an axle device of a wheel loader. The axle device 200 may also be an axle device of a dump truck.

[0084] 6 is a cross-sectional view of the axle device 200. As shown in FIG. 6, the axle device 200 has a differential mechanism 210, a main body case 220, and a rotating shaft 230.

[0085] The differential mechanism 210 is disposed inside the main body case 220. The differential mechanism 210 has gear cases 211a and 211b, a spider 212, a pinion gear 213, side gears 214a and 214b, rotating shafts 215a and 215b, and a ring gear 216.

[0086] The gear case 211a and the gear case 211b are attached to the rotating shaft 215a and the rotating shaft 215b, respectively. The main body case 220 has a partition wall 221a and a partition wall 221b. The gear case 211a and the gear case 211b are rotatably supported by the main body case 220 via a rolling bearing 100A. More specifically, the inner ring 110 is attached to the gear case 211a (gear case 211b), and the outer ring 120 is attached to the partition wall 221a (partition wall 221b).

[0087] The spider 212 is disposed in a space defined by the gear case 211a and the gear case 211b. The pinion gear 213 is rotatably attached to the spider 212. The side gears 214a and 214b mesh with the pinion gear 213. The side gears 214a and 214b are attached to the rotation shafts 215a and 215b, respectively. The ring gear 216 is attached to the gear case 211a. The ring gear 216 is a bevel gear.

[0088] The rotating shaft 230 has a pinion gear 231 at its tip. The pinion gear 231 meshes with the ring gear 216. The rotating shaft 230 is rotatably supported in the main body case 220 by a rolling bearing. When the rotating shaft 230 rotates, the rotation of the rotating shaft 230 is transmitted to the rotating shaft 215a via the pinion gear 231, the ring gear 216, and the gear case 211a, causing the rotating shaft 215a to rotate. In addition, the rotation of the rotating shaft 215a is transmitted to the rotating shaft 215b via the side gear 214a, the pinion gear 213, and the side gear 214b, causing the rotating shaft 215b to rotate together with the gear case 211b.

[0089] By changing the rotation direction of the rotating shaft 230, the rotation direction of the rotating shafts 215a and 215b (gear cases 211a and 211b) also changes. Therefore, in the rolling bearing 100A, the inner ring 110 rotates forward and backward relative to the outer ring 120. Also, in the axle device 200, the rotating shaft 230 is repeatedly rotated and stopped, so that in the rolling bearing 100A, the inner ring 110 rotates relative to the outer ring 120 from a stationary state.

[0090] As described above, the rolling bearing 100A is used under conditions where oil film breakdown is likely to occur because the inner ring 110 rotates in both directions relative to the outer ring 120 and the inner ring 110 rotates from a stationary state to the outer ring 120 repeatedly. More specifically, the rolling bearing 100A is used under conditions where the oil film parameter (Λ) is less than 1.2 or the dn value (the value obtained by multiplying the inner diameter of the inner ring 110 in mm by the rotation speed of the inner ring 110 in rpm) is 200,000 or less.

[0091] Under conditions where oil film breakdown is likely to occur, the surfaces of the inner ring 110 (raceway surface 110da) and the outer ring 120 (raceway surface 120ca) come into metallic contact with the surfaces of the rolling elements 130, and wear tends to cause new surfaces to form on the surfaces of the inner ring 110, the outer ring 120, and the rolling elements 130. Hydrogen is likely to be generated from the lubricating oil on the new surfaces, and this hydrogen penetrates through the new surfaces, causing hydrogen embrittlement on the surfaces of the inner ring 110, the outer ring 120, and the rolling elements 130.

[0092] However, because precipitates are dispersed at high density in the steel of the surface layer of the inner ring 110, the surface layer of the outer ring 120, and the surface layer of the rolling elements 130, wear is unlikely to progress even under conditions where oil film breakdown is likely to occur. In addition, the precipitates dispersed in the steel of the surface layer of the inner ring 110, the surface layer of the outer ring 120, and the surface layer of the rolling elements 130 act as trap sites for hydrogen atoms, reducing the amount of hydrogen penetration in the surface layer of the inner ring 110, the surface layer of the outer ring 120, and the surface layer of the rolling elements 130. Therefore, with the rolling bearing 100A, it is possible to suppress the occurrence of early flaking caused by hydrogen embrittlement.

[0093] In addition, in rolling bearing 100A, the volume ratio of retained austenite in the steel is 15 percent or more (25 percent or more and 35 percent or less) at a position where the distance between the surfaces of inner ring 110, outer ring 120, and rolling element 130 is 50 μm, thereby improving durability against impression-induced peeling in an environment containing foreign matter.

[0094] (Rolling fatigue life test) In order to confirm the effect of the bearing part according to the embodiment, a rolling fatigue life test was carried out. Samples 1, 2, and 3 were used in the rolling fatigue life test. Samples 1 to 3 are thrust ball bearings of model number 51106 defined by the JIS standard.

[0095] In sample 1, the races (inner ring and outer ring) were formed from the first steel material. In samples 2 and 3, the races were formed from the second steel material. The compositions of the first and second steel materials are shown in Table 1. As shown in Table 1, the components of the first and second steel materials are almost identical except for the molybdenum and vanadium contents. The second steel material corresponds to SUJ2, a high carbon chromium bearing steel defined in the JIS standard.

[0096] [Table 1]

[0097] Fig. 7 is a graph showing the measurement results of the nitrogen concentration and carbon concentration in the vicinity of the raceway surface of the race of Sample 1. Fig. 8 is a graph showing the measurement results of the nitrogen concentration and carbon concentration in the vicinity of the raceway surface of the race of Sample 2. The horizontal axis of Fig. 7 and Fig. 8 is the distance from the raceway surface (unit: mm), and the vertical axis of Fig. 7 and Fig. 8 is the carbon or nitrogen concentration (unit: mass percent). As shown in Fig. 7 and Fig. 8, in Sample 1 and Sample 2, nitriding treatment was performed on the surface of the race. The heating temperature during this nitriding treatment was 850°C. On the other hand, in Sample 3, nitriding treatment was not performed on the surface of the race.

[0098] Table 2 shows the nitrogen concentration in the surface layer (region up to 20 μm away from the raceway surface) of Samples 1 to 3. As shown in Table 2, the nitrogen concentration in the steel of the surface layer of the race of Samples 1 and 2 was 0.3 percent or more and 0.5 percent or less. The nitrogen concentration in the steel of the surface layer of the race of Sample 3 was 0.0 percent.

[0099] [Table 2]

[0100] The bearing races of Samples 1 to 3 were subjected to quenching and tempering. The heating temperature during quenching was 850° C. The heating temperature during tempering was 180° C. The heating time during tempering was 2 hours.

[0101] Figure 9 is an SEM image of the surface layer of the race of Sample 1. Figure 10 is an SEM image of the surface layer of the race of Sample 2. In the SEM images of Figures 9 and 10, the white areas are precipitates, and the elliptical grey areas are cementite.

[0102] As shown in Table 3, the area ratio of precipitates in the steel of the surface layer of the race of Sample 1 was 2.7 percent. As shown in Table 3, the area ratio of precipitates in the steel of the surface layer of Sample 2 was 1.6 percent. In other words, precipitates were dispersed at a higher density in the surface layer of the race of Sample 1 compared to the surface layer of the race of Sample 2. This comparison reveals that by adding 0.5 mass percent or less of vanadium and molybdenum, precipitates are dispersed at a higher density in the steel of the surface layer of the race.

[0103] The maximum grain size of precipitates in the surface layer of the race of Sample 1 was 0.5 μm. The maximum grain size of precipitates in the surface layer of the race of Sample 2 was 1.1 μm. In other words, the precipitates were more finely dispersed in the surface layer of the race of Sample 1 compared to the surface layer of the race of Sample 2. This comparison reveals that by adding 0.5 mass percent or less of vanadium and molybdenum, the precipitates are densely and finely dispersed in the steel in the surface layer of the race.

[0104] [Table 3]

[0105] As shown in Table 4, the maximum grain size of cementite was 1.5 μm or less in the surface layer of the race of Sample 1 and Sample 2. The maximum grain size of cementite in the surface layer of the race of Sample 3 exceeded 1.5 μm.

[0106] [Table 4]

[0107] As shown in Table 5, in Samples 1 and 2, the volume ratio of retained austenite in the steel at a position 50 μm away from the raceway surface was 15 percent or more. In Sample 3, the volume ratio of retained austenite in the steel at a position 50 μm away from the raceway surface was less than 15 percent. In Samples 1 to 3, the hardness of the steel at a position 50 μm away from the raceway surface was 58 HRC or more.

[0108] [Table 5]

[0109] FIG. 11 is an EBSD phase map of the surface layer of the race of Sample 1. FIG. 12 is an EBSD phase map of the surface layer of the race of Sample 2. FIG. 13 is an EBSD phase map of the surface layer of the race of Sample 3. In FIGS. 11 to 13, the martensite block grains are shown in white. FIG. 14 is a bar graph showing the average grain size of the martensite block grains in the surface layer of the races of Samples 1 to 3. The vertical axis of the graph in FIG. 14 is the average grain size (unit: μm) of the martensite block grains.

[0110] 11 to 14, in the surface layer portion of the race of Sample 1, the average grain size of the martensite block grains was 2.0 μm or less when the comparative area ratio was 30 percent. On the other hand, in the surface layer portions of the races of Sample 2 and Sample 2, the average grain size of the martensite block grains was more than 2.0 μm when the comparative area ratio was 30 percent.

[0111] In the surface layer of the race of Sample 1, the average grain size of the martensite block grains at a comparative area ratio of 50 percent was 1.5 μm or less. On the other hand, in the surface layer of the race of Sample 2 and Sample 3, the average grain size of the martensite block grains at a comparative area ratio of 50 percent exceeded 1.5 μm.

[0112] Figure 15 is a graph showing the results of the rolling fatigue life test. The horizontal axis of the graph in Figure 15 indicates the life (unit: hours), and the vertical axis of the graph in Figure 15 indicates the cumulative failure probability (unit: percentage). The rolling fatigue life test was conducted under the conditions shown in Table 6. That is, the maximum contact pressure between the rolling elements and the race was 2.3 GPa, the race was rapidly accelerated and decelerated between 0 rpm and 2500 rpm, and the lubricant used was polyglycol oil mixed with pure water.

[0113] [Table 6]

[0114] As shown in FIG. 15 and Table 7, Sample 1 exhibited a better rolling contact fatigue life than Sample 2. More specifically, the L 10 The lifespan (lifespan at which the cumulative probability of failure is 10 percent) is L for sample 3. 10 The L of sample 2 is 2.7 times the lifespan. 10 The life span is L for sample 3 10 This was 2.1 times the expected lifespan.

[0115] As described above, the average grain size of martensite grains at a comparative area ratio of 30 percent was 2.0 μm or less in the surface layer portion of the race of Sample 1. On the other hand, the average grain size of martensite grains at a comparative area ratio of 30 percent exceeded 2.0 μm in the surface layer portions of the races of Samples 2 and 3. This comparison makes it clear that the bearing component according to the embodiment has improved durability.

[0116] [Table 7]

[0117] Also, as described above, in the surface layer portion of the race of Sample 1, the precipitates were finer and more densely dispersed than in the surface layer portion of the race of Sample 2. From this comparison, it became clear that the durability of the bearing component according to the embodiment can be further improved by setting the area ratio and maximum grain size of the precipitates in the surface layer portion to 2.0 percent or more and 0.5 μm or less, respectively.

[0118] Also, L of sample 2 10 The life span is L for sample 3. 10As mentioned above, the maximum grain size of cementite in the surface layer of the race of Sample 2 was 1.5 μm or less, while the maximum grain size of cementite in the surface layer of the race of Sample 3 exceeded 1.5 μm. Also, in the race of Sample 2, the volume ratio of retained austenite at a position 50 μm away from the raceway surface was 15 percent or more, while in the race of Sample 3, the volume ratio of retained austenite at a position 50 μm away from the raceway surface was less than 15 percent.

[0119] This comparison revealed that the durability of bearing components can be improved by setting the maximum grain size of cementite in the surface layer of the bearing components to 1.5 μm or less and setting the volume ratio of retained austenite to 15 percent or more at a position 50 μm away from the surface of the bearing components.

[0120] <Hydrogen penetration characteristics> The hydrogen penetration characteristics of the surface layers of the raceway members (inner ring and outer ring) of Sample 1 and Sample 3 were evaluated by the following method. In this evaluation, firstly, the raceway members of Sample 1 and Sample 3 before being subjected to the above-mentioned rolling fatigue life test were heated from room temperature to 400°C to measure the amount of hydrogen released from the raceway members of Sample 1 and Sample 3 before being subjected to the rolling fatigue life test. Secondly, the raceway members of Sample 1 and Sample 3 after being subjected to the rolling fatigue life test for 50 hours were heated from room temperature to 400°C to measure the amount of hydrogen released from the raceway members of Sample 1 and Sample 3 after being subjected to the rolling fatigue life test for 50 hours.

[0121] In Sample 3, the ratio of the amount of hydrogen released before and after the rolling fatigue life test (i.e., the value obtained by dividing the amount of hydrogen released after being subjected to the rolling fatigue life test by the amount of hydrogen released before being subjected to the rolling fatigue life test) was 3.2. On the other hand, in Sample 1, the ratio of the amount of hydrogen released before and after the rolling fatigue life test was 0.9. From this comparison, it was experimentally clarified that the formation of surface layer 11 on the contact surface suppresses hydrogen penetration into surface layer 11, and suppresses early flaking due to hydrogen embrittlement.

[0122] Although the embodiment of the present invention has been described above, the above embodiment can be modified in various ways. The scope of the present invention is not limited to the above embodiment. The scope of the present invention is defined by the claims, and is intended to include all modifications within the meaning and scope of the claims. [Industrial Applicability]

[0123] This embodiment is particularly advantageously applicable to a bearing component and a rolling bearing having the same. [Explanation of symbols]

[0124] 10 inner ring, 10a, 10b width, 10c inner circumference, 10d outer circumference, 10da raceway, 11 surface, 20 outer ring, 20a, 20b width, 20c inner circumference, 20ca raceway, 20d outer circumference, 30 rolling elements, 40 cage, 100 rolling bearing, A center shaft, S1 Preparation process, S2 nitriding process, S3 quenching process, S4 tempering process, S5 post-treatment process, 100A rolling bearing, 110 inner ring, 110a,110b width surface, 110c inner peripheral surface, 110d outer peripheral surface, 110da raceway surface, 120 outer ring, 120a,120b width surface, 120c Inner surface, 120ca Raceway surface, 120d Outer circumferential surface, 130 rolling element, 140 retainer, 200 axle device, 210 differential mechanism, 211a, 211b gear case, 212 spider, 213 pinion gear, 214a, 214b side gear, 215a, 215b rotating shaft, 216 ring gear, 220 main body case, 221a, 221b partition wall, 230 rotating shaft, 231 pinion gear.

Claims

1. A rolling bearing comprising an inner ring, an outer ring, and rolling elements, the rolling bearing being attached to a mechanical structure in which the inner ring rotates forward and backward relative to the outer ring, or the inner ring rotates relative to the outer ring from a stationary state, At least one of the inner ring, the outer ring, and the rolling elements is made of steel and has a surface layer portion that is a region up to 20 μm away from a surface, The steel comprises 0.70 to 1.10 percent by weight carbon, 0.15 to 0.35 percent by weight silicon, 0.30 to 0.60 percent by weight manganese, 1.30 to 1.60 percent by weight chromium, 0.20 to 0.50 percent by weight vanadium, 0.10 to 0.50 percent by weight molybdenum, and the balance being iron and unavoidable impurities; The steel of the surface layer portion has martensite block grains and precipitates, the precipitate is a nitride containing chromium or vanadium as a main component, or a carbonitride containing chromium or vanadium as a main component, In the steel of the surface layer portion, the average grain size of the martensite block grains at a comparative area ratio of 30 percent is 2.0 μm or less, The rolling bearing is used under conditions in which the oil film parameter is less than 1.

2.

2. 2. The rolling bearing according to claim 1, wherein the rolling bearing is used under conditions in which a dn value is 200,000 or less.

3. 3. The rolling bearing according to claim 1, wherein the rolling bearing is a tapered roller bearing.

4. 3. The rolling bearing according to claim 1, wherein the rolling bearing is a spherical roller bearing.

5. 5. The rolling bearing according to claim 1, wherein the surface is provided with a diamond-like carbon coating or an iron oxide coating.

6. The rolling bearing according to any one of claims 1 to 5, wherein the steel contains 0.90 mass percent to 1.10 mass percent carbon, 0.20 mass percent to 0.30 mass percent silicon, 0.40 mass percent to 0.50 mass percent manganese, 1.40 mass percent to 1.60 mass percent chromium, 0.20 mass percent to 0.30 mass percent vanadium, 0.10 mass percent to 0.30 mass percent molybdenum, and the balance being iron and unavoidable impurities.

7. 7. The rolling bearing according to claim 1, wherein an area ratio of the precipitates in the steel of the surface layer portion is 2.0 percent or more.

8. The rolling bearing according to any one of claims 1 to 7, wherein the precipitates in the steel of the surface layer have a maximum grain size of 0.5 µm or less.

9. The steel of the surface layer portion further has cementite, The rolling bearing according to any one of claims 1 to 8, wherein the cementite in the steel of the surface layer portion has a maximum grain size of 1.5 µm or less.

10. The rolling bearing according to any one of claims 1 to 9, wherein the nitrogen concentration in the steel of the surface layer is 0.15 mass percent or more.

11. 11. The rolling bearing according to claim 1, wherein a volume ratio of retained austenite in the steel at a position 50 μm away from the surface is 15% or more.

12. 12. The rolling bearing according to claim 1, wherein the hardness of the steel is 58 HRC or more at a position 50 μm away from the surface.

13. At a position 50 μm away from the surface, the volume ratio of retained austenite in the steel is 25% or more and 35% or less, 13. The rolling bearing according to claim 1, wherein the hardness of the steel at a position 50 μm away from the surface is 58 HRC or more and 64 HRC or less.

Citation Information

Patent Citations

  • Combustion method of externally ignited fuel for air compressed direct injection type internal combustion engine

    JP1979089111A

  • Glycidyl ester-allylglycidyl ether copolymer

    JP1985023422A

  • Bearing component

    JP2014152378A

  • Bearing parts, and roller bearing

    JP2019108576A

  • Steel component excellent in rolling fatigue characteristics

    JP2019167551A